Perceived factors contributing to teenage pregnancy and their perceived effects on teenage females health in eastern province of Rwanda - Claudine Nshutiyukuri; Fauste Uwingabire; Marie Grace Sandra Musabwasoni; Jean Bosco Rutayisire; Reverien Rutayisire; Immaculée Benimana; Gerard Kaberuka; Laetitia Bazakare Ishimwe; Kyamusoke Borauzima Kyame; Leon Mutabazi; Madeleine Mukeshimana (Women's Health)
Background: Teenage girls in Rwanda, like in many other countries, continue to experience unintended pregnancies. Many adolescents exhibit inadequate knowledge regarding sexual and reproductive health, highlighting significant gaps in its use specifically in developing regions including Rwanda. Despite the implementation of numerous prevention strategies in Rwanda, the prevalence of teenage pregnancy remains alarmingly high. The factors contributing to teenage pregnancy are diverse, and its consequences are far-reaching. Objective: This study’s primary objective is to examine participants’ personal experiences with their own pregnancies, including the factors they perceive to have contributed to their pregnancies. Additionally, the study aims to investigate participants’ views on the broader societal factors that they believe contribute to teenage pregnancy within their community or province. Design: A cross-sectional study design was used. Methods: A cross-sectional study was conducted in the Eastern Province of Rwanda, between January and December 2023. The sample included females aged 13–25 years who described their own pregnancies when they were between 13 and 19 years, as well as their perceptions about other pregnancies in their community. Data were collected using a structured questionnaire and analyzed through descriptive statistical methods. Results: Teenage girls reported poverty and lack of knowledge as the leading causes of adolescent pregnancy, with a high percentage of them reporting that their pregnancies resulted from rape. The effects of teenage pregnancy on teenage female health include emotional and societal repercussions with a high prevalence of depression, suicidal thoughts, family rejection, and school dropouts. The scope of this study was limited to teenage mothers in Eastern province and all data came from their self-reporting. Conclusion: Poverty, lack of knowledge, and sexual violence/rape were the most frequently perceived causes of adolescent pregnancy reported by participants, with important consequences for the health and well-being of teenage girls and their children. Comprehensive teenage pregnancy preventive interventions involving men would address the root causes of teenage pregnancy and improve health literacy as regard to sexual and reproductive health. There is a need for an urgent governmental and private joint plan to reduce the burden of teenage pregnancy in Rwanda.